The influence of economic growth, energy consumption, poverty and population on Indonesia's environmental quality index - Susanti Tasri, Evi; Karimi, Kasman; Muslim, Irwan; Dwianda, Yudi (KnE Social Sciences, 2022)
The quality of the environment is very important for the sustainability of a country’s economic development, and the environment is influenced by macroeconomic indicators. This study aimed to analyze the effect of economic growth, energy consumption, poverty and population on Indonesia’s quality of environment index. The data used in this research were secondary data and multiple linear regression was used to analyze the data. Based on the results, energy consumption and population have a significant effect on the index of the quality of the living environment in Indonesia. Meanwhile, the variables of economic growth and poverty have a partially insignificant effect on this index. So the results provide empirical evidence that environmentally friendly energy consumption actions have been well managed. The population was found to have a negative effect on environmental quality, perhaps partly due to irresponsible exploitation by residents where natural resources have became an easy choice for fulfilling needs. These actions must be recognized as damaging the environment and threatening the survival of life. Keywords: environmental quality index, economic growth, population, poverty, energy consumption